Digital lighting and rendering - Birn, Jeremy, ....- (Berkeley : New Riders, 2014)
Learn the fine art and craft of digital lighting and rendering from an experienced pro whose lighting work you've seen in blockbuster films such as Monsters University, Toy Story 3, Up, WALL-E, Ratatouille, and The Incredibles. Jeremy Birn draws on his wealth of industry and teaching experience to provide a thoroughly updated edition of what has become the standard guide to digital lighting and rendering. Using beautiful, full-color examples; a friendly, clear teaching style; and a slew of case studies and tutorials, Jeremy demonstrates how to create strategic lighting for just about any project using any 3D application. By explaining not just how to use various lighting techniques but why, this guide provides the grounding graphics pros need to master Hollywood lighting techniques.
Keywords: Computer graphics; Light -- Computer simulation; Three-dimensional display systems